Quality of antenatal care provided through the public health sector in a district in North Kerala - ali Mundodan, Jesha Mohammed (Public Health Review: International Journal of Public Health Research, 2017)
Introduction: Quality of Care, a key element in provision of health care can be assessed by using technical standards defined by health professionals or from client’s perspective. Considering the population in Kerala to have advantage of early and nearly universal antenatal coverage, there is considerable potential for improving the quality of care, based on regular quality assessment. Objectives: 1.To evaluate observed quality of process of ante-natal care at various levels in the public health sector of Kozhikode district of Kerala. 2. To find out the perception of antenatal women regarding the antenatal care provided. Methodology: A cross sectional study was conducted in maternal health care institutions at various levels in the public health sector of Kozhikode district, North Kerala. Arbitrarily, 30% of institutions were selected from each stratum. Observed quality of antenatal care was assessed through passive observation of services delivered with help of a checklist. 197 antenatal women were observed. All antenatal women who had come for their re-visit were interviewed for assessing client perspective of quality of care. Hence 93 antenatal women were interviewed excluding those who had come for first visit. Results: Overall score for attributes of process of antenatal care was observed to be poor. Interpersonal aspects scored better. There was significant difference between different strata (p <0.001), with better scores at Taluk Hospital and Block Primary Health Centre levels and the difference in scores was found to be significant with regards to Diagnostic-techniques, Treatment-aspects, provision-of-Health-Education. An evident disparity was noted between observed and client’s perspective. 92.47% were satisfied with overall care. More than three-fourth were satisfied with time spent with health care provider though most spent only 5–15 minutes. Conclusion: Quality of antenatal care delivery needs to be improved.